Investigating the Dietary Flexibility and Feeding Behavior of Clarias anguillaris and Auchenoglanis biscutatus in a Tropical River Ecosystem - Tivfa Samuel Gbaior; Joel Inya Odo; Charles Ifeanyi Odoh; Edward Terhemen Akange; Ayush Madan (International Journal of Marine Life, 2025)
Studies on food and feeding habits of fishes are required to guide the selection of fish species for culture. The current study determined the food and feeding habits of Clarias anguillaris and Auchenoglanis biscutatus in the Lower River Benue at Makurdi, Nigeria. Fish samples were collected biweekly from local fishermen at the Wadata landing site who fished with different gears like gillnets, cast nets, hook and line, traps and lift nets. Fish specimens were collected and transported in ice boxes to the laboratory for dissection and identification using a stereoscopic microscope. Percentages of food items for C. anguillaris ranged from sand/mud (3.75%) to Daphnia and insects (14.29%) using the frequency of occurrence method, the numerical method recorded a range of sand/mud (2.63%) and Daphnia (15.46%) while the volumetric method range was between detritus (2.86 %) and insects (whole/parts) with 7.77%. Results of the frequency of occurrence, numerical, and volumetric methods for A. biscutatus ranged from Daphnia and insects (7.10% each) – sand/mud (13.55%), plant materials (4.61%) – Annelids (15.46%) and Algae (2.77%) – sand/mud (18.14%), respectively. Dietary overlap analysis revealed notable similarities between the fish species, especially for insect parts and detritus. The high index of relative importance (IRI) values for specific food items showed that both fish species exhibited the omnivorous and opportunistic feeding habit. It is therefore concluded that both fish species are valuable choices for culture, having high dietary variability.
Keywords: Food sources; dietary overlap; ecological stability; fish and adaptability; stomach content analysis